История Санкт-Петербурга: [школьный путеводитель] / С. А. Прохватилова - Прохватилова Светлана Алексеевна (Узнай мир, 2011)
Экземпляры: аб. (20221027) / Инвентарный номер: 62702 / Цена: / Сис.шифр: 63.3(2-2СПб) / Авт.знак: П 84 / ГРНТИ: 03.23 / ББК: 63.3(2-2СПб)я2